Integrative analyses of 16S rDNA sequencing and serum metabolomics demonstrate significant roles for the oral microbiota and serum metabolites in post-kidney transplant diabetes mellitus - Chao Liu; Sheng Chao; Lei Jia; Qizhen Yang; Qian Chen; Yulin Niu (Microbiology Spectrum, 2025)
ABSTRACT Oral microbiota and serum metabolites play crucial roles in diabetes, but their relationship with post-transplant diabetes mellitus (PTDM), a common complication post-kidney transplantation, is not well characterized. This study investigated the relationship of oral microbiota and serum metabolites with PTDM using integrative analysis of 16S rDNA sequencing and serum metabolomics. We recruited 61 kidney transplant recipients, including 30 in the PTDM group and 31 in normal glucose tolerance controls. Oral samples and serum samples were collected from all the kidney transplant patients to perform 16S rDNA sequencing and serum metabolomics analysis. We annotated 689 oral microbial species, including 134 species unique to the PTDM group and 157 species unique to the control group. PTDM group showed upregulation of 36 metabolites and downregulation of 19 metabolites. Based on the random forest machine learning algorithm, genera such as UCG−005 (AUC = 0.9355), Succinivibrio (AUC = 0.8108); Akkermansia (AUC = 0.7742), Anaerovibrio (AUC = 0.2667), and Schwartzia (AUC = 0.2667), and serum metabolites such as LPI 18:0 (AUC: 0.8086), methylglyoxal (AUC: 0.7946), Vulgarin (AUC: 0.7828), 2-mercaptobenzothiazole (AUC: 0.7591), and PI(18:0/20:3(5Z,8Z,11Z)) (AUC: 0.7419) showed high diagnostic potential and may serve as clinical biomarkers. Furthermore, clinical indicators in PTDM patients, such as creatinine, cystatin C, and urea, showed a significant association with the differential oral microbiota and serum metabolites. Dysbiosis in the oral microbiota of the PTDM patients was associated with changes in the serum metabolites and alterations in their functions. These findings provide new insights toward identifying mechanisms by which oral microbiota and serum metabolites contribute to the development of PTDM.IMPORTANCEThis study reveals an imbalance in oral microbiota in patients with post-transplant diabetes and uncovers the potential relationship between oral microbiota and serum metabolites. These findings provide new insights into the role of oral microbiota and serum metabolites in the treatment of post-transplant diabetes, offering relevant biomarkers for clinicians and future research.